Application and analysis of interacting multimode Kalman filter in location algorithm. (August 2020) - Ning, Xiao
Abstract: Aiming at the non-line-of-sight (NLOS) problem that affects the accuracy of wireless location in cellular networks, the IMM method is introduced. The method based on interactive multimode Kalman filter (IMMKF) is studied and analyzed in detail. A more complex second-order and fourth-order Markov transfer model is established to describe the wireless communication channel. The positioning performance and the factors that affect the performance of IMMKF filter are analyzed by simulation. The simulation results show that IMMKF can adaptively switch between models with the change of channel propagation environment, suppress non line of sight error, and show good positioning performance and filtering performance.